MEDU-17. HIGH IMPACT OF miRNA-4521 ON FOXM1 EXPRESSION IN MEDULLOBLASTOMA. (23rd April 2019) - Madlener, Sibylle; Senfter, Daniel; Samadaei, Mahzeiar; Mader, Robert M; Gojo, Johannes; Peyrl, Andreas; Krupitza, Georg; Kool, Marcel; Sill, Martin; Haberler, Christine; Ricken, Gerda; Czech, Thomas; et al.
Abstract: Medulloblastoma, an embryonal tumor of the cerebellum/fourth ventricle, is one of the most frequent malignant brain tumors in children. Although knowledge of genetic variants increased over recent years and starts to be reflected in treatment stratification, survival of high-risk patients with leptomeningeal dissemination, TP53 mutation or MYC amplification is still poor. FOXM1, a proliferation-specific oncogenic transcription factor, is dysregulated in many different solid tumors, including medulloblastoma, and triggers proliferation, migration and genomic instability in the cells. We investigated the effect of miRNA-4521, located on chromosome 17p, on the expression of FOXM1 in medulloblastoma cell lines and describe a link between the downregulated miRNA-4521 and the dysregulated transcription factor FOXxM1 in medulloblastoma. Our results indicate a high impact of miRNA-4521 on FOXM1 protein expression. Transfection of this miRNA reduced the proliferation and invasion of several medulloblastoma cell lines and induced programmed cell death through the activation of the caspase 3/7. Further, the downstream targets of FOXM1 such as PLK1 and cyclin B were significantly reduced and affected the cell cycle progression in medulloblastoma cell lines. In conclusion, a restoration of miRNA-4521 may provide a targeted approach for medulloblastoma therapy.